THE COSTA RICAN CRIMINAL PROCEDURAL LAW. ITS DOCTRINARY EVOLUTION AND ACADEMICAL TEACHING - Gatgens Gómez, Erick (2023)
In this article written on the occasion of the 60th anniversary of the Revista de Ciencias Jurídicas, we seek to demonstrate the scientific evolution and academic teaching of Criminal Procedure Law in our country, through a tour of the texts published in the aforementioned journal during these sixty. years, temporarily located and referenced according to the legislation in force at that time, namely, the General Code of 1841, the Code of Criminal Procedures of 1973 and the Criminal Procedure Code of 1996. At the end some conclusions are issued and the bibliography is included used in the preparation of the article.